(3GdNdGUIs - (3WGgQ Hf CMeO Hf YHO GdQTjO Hf GdMSjf, GaJNGQ GdOjf GdHNGQj,J (B542 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCQhGM hGdCLSGe hLGYd GdfhQ hGdXdGe s
(3BNQgG (B:s
(3hGddg CYde HGdUhGH s
(3HChdg agQSJ ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B32s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs